Toxic effects of herbicides on transplanted paddy - Thapa, Chandra Bahadur (Nepalese Journal of Biosciences, 2013)
The effectiveness of two herbicides viz., 2 4-D and butachlor for the control of weeds in transplanted paddy and improving the grain yield was studied. Slight toxic effect of herbicides on paddy plants was noticed at 21 days after transplanting of paddy seedlings. However, it didn’t persist for long and had no overall harmful effect on grain yield. Both the herbicides produced satisfactory control of the weed population and dry matter. This resulted in a significant increase in grain yield over un-weeded control. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7483 Nepalese Journal of Biosciences 2 : 5-9 (2012)